Efficacy of Ultrasound-Guided Injection of Platelet-Rich Plasma in Treatment of Sports-Related Meniscal Injuries - Prabakar Singh Raju; Makesh Ram Sriraghavan; Pazhani Jayaraman; Bheeshma Balasubramaniam; Karthik Shanmugavel Karuppiah; Poornima Kumararaja (Indian Journal of Radiology and Imaging)
Purpose Meniscal injuries are a common occurrence in sports-related activities, often leading to pain, reduced joint function, and impaired athletic performance. This study aimed to evaluate the role of ultrasound-guided intra-articular platelet-rich plasma (PRP)-rich fluid injection which was obtained through serial centrifugation in the treatment of meniscal injuries resulting from sports activities.